Dấu hiệu các bờ biển cổ ở đáy biển nông ven bờ Bắc Trung Bộ vỡ tiềm năng sa khoáng liên quan - Phúc, La Thế; Sơn, Vũ Trường (Vietnam Journal of Earth Sciences, 2008)
Traces of the buried Late Pleistocene ancient coastline in the coastal shallow bed of the North Central part of Vietnam and associated placer potential